The Influence of Brand Equity and Price on Repurchase Interest Through Customer Satisfaction as an Intervening Variable on Samsung Smartphones in Generation Z, Bandung City - Juningsih Juningsih; Sri Astuti Pratminingsih (Dinasti Publisher, 2025)
This study aims to determine brand equity and price on repurchase Interest through customer satisfaction as an intervening variable on Samsung Smartphones in Generation Z in Bandung City. This type of research uses descriptive and verification methods, with a quantitative approach with data processing through the IBM SPSS Version 27 program, the sampling technique uses probability sampling to be more precise using simple random sampling. The number of samples is 385 people, namely consumers who have purchased Samsung brand smartphones. The data analysis method in this study uses multiple linear regression analysis and path analysis to determine the direction of the relationship between the brand equity variable (X1) and the price variable (X2) with the repurchase Interest variable (Y) through customer satisfaction (Z) as an intervening variable. The results of this study indicate that brand equity and price have a positive and significant effect on repurchase Interest through customer satisfaction on Samsung brand smartphones in Generation Z in Bandung City. the results of the multiple determination coefficient based on the results of data processing of 60.2% of the amount of repurchase Interest in generation Z in Bandung City is influenced by both independent variables, namely brand equity and price, through customer satisfaction, while the remaining 39.8% is influenced by other variables.